2012
DOI: 10.1128/aem.00548-12
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Maturation of Hyperthermophilic Pyrolysin and the Roles of Its N-Terminal Propeptide and Long C-Terminal Extension

Abstract: ABSTRACTPyrolysin-like proteases from hyperthermophiles are characterized by large insertions and long C-terminal extensions (CTEs). However, little is known about the roles of these extra structural elements or the maturation of these enzymes. Here, the recombinant proform ofPyrococcus furiosuspyrolysin (Pls) and several N- and C-terminal deletion mutants were successfully expressed in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The stabilizing effect of IS8 on pyrolysin is closely related to its involvement in electrostatic interactions important for structural integrity of the enzyme. Our previous study demonstrated that the CTE of pyrolysin confers additional enzyme stability (12). Because IS8 is located near the C terminus of the catalytic domain and resides within a surface loop (11), it could be involved in the interaction between the catalytic domain and the CTE, conferring additional enzyme stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stabilizing effect of IS8 on pyrolysin is closely related to its involvement in electrostatic interactions important for structural integrity of the enzyme. Our previous study demonstrated that the CTE of pyrolysin confers additional enzyme stability (12). Because IS8 is located near the C terminus of the catalytic domain and resides within a surface loop (11), it could be involved in the interaction between the catalytic domain and the CTE, conferring additional enzyme stability.…”
Section: Discussionmentioning
confidence: 99%
“…4E). We showed previously that only correctly folded proforms of pyrolysin matured efficiently and that the proform is less stable than the mature form with respect to thermogenic hydrolysis resistance (12). Given this information, the low maturation efficiencies of the Ca4 site variants (e.g., D163A and D161N/D163N/D165N) could be due to slower folding and lower maturation rates compared to those of the WT.…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…Multiple mature forms have been described for other CTEcontaining subtilases, such as Vpr (31,32) and Epr (33,34) from B. subtilis and pyrolysin from Pyrococcus furiosus (35,36). Maturation of these enzymes also involves differential proteolytic processing of the CTE.…”
Section: Discussionmentioning
confidence: 99%
“…The Tk-subtilisin and alkaline serine protease exhibited optimum enzymatic activity at 90°C and 100°C and halflives at 100°C of 50 min and 100 min, respectively. Pyrolysin from Pyrococcus furiosus had a half-life value of 4 h at the boiling point of water (Voorhorst et al, 1996;Dai et al, 2012). An aeropyrolysin (a metalloproteinase) from Aeropyrum pernix K1 (an aerobic marine hyperthermophilic archaeon) had a maximum activity at 110°C.…”
Section: Hyperthermophilic Archaeamentioning
confidence: 99%